Acquisition of Word-formation Competence by Children Aged 3 to 6 Based on the Example of nomina agentis - Siudzińska, Natalia; Jankowska, Ewelina (Slavistica Vilnensis, 2022)
The article presents how preschool children (aged 3 to 6) develop word-formation competences in the category of nomina agentis (names of agents). The linguistic material was collected with the author’s questionnaire. The tasks in this questionnaire were preceded by an example that led the child to the correct word formation scheme. The quantitative and qualitative analysis was created with the division into verbal formants (-acz and -ator) and nominal formants (-arz and -owiec). The analysis included the coding (creation) and decoding (an indication of the motivating word) of derivatives.The research showed how the process of acquiring word formation skills worked in the case of preschool children (aged 3 to 6) of similar social backgrounds. They confirmed that their word-building competence increased linearly, indicated the age at which they start developing these functions and what strategies they used when they were unable to complete the tasks. Among the 1,280 researched utterances, the most common children’s operations were the creation of tranpositional derivatives (e.g. słuchanie), neologisms (e.g. organizacz, organizek, organizant; dokuczaniec, dokucznik; mydłowiec), alternation and adding connectives (e.g. zabaw-l-owiec; kostk-ow-ek). The conclusions reached after the analysis of the material were compared with the hypotheses found in the literature on the subject matter and with the results of other researchers.